Legal Analysis of Unpaid Loss Insurance Claims Against Rental Cars - Muhammad Dhobit Azhary Lubis; Sarah Furqoni (IHSA Institute, 2022)
A loss insurance claim is a form of the insured's right to demand compensation for an insurance object that experiences an event, namely an uncertain event, it can be an accident, damages that have been stated in the policy, even fatally the insurance object is lost. Submitting an insurance claim for the insured must first complete the requirements for filing a loss insurance claim such as the necessary documents, facts that actually occurred at the scene of the case where all of these requirements can be seen in the policy.The purpose of this study is to find out how the form of a loss insurance policy for rental cars is, how to submit a loss insurance claim against rental cars, and how to analyze the law of unpaid loss insurance claims against rental cars. To achieve the research objectives, a juridical research was conducted, namely data analysis that revealed and retrieved the truth obtained from the literature by combining regulations, scientific books that had to do with the